2018
DOI: 10.1186/s12918-018-0651-1
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA expression profiles during the differentiation of mouse neural stem cells

Abstract: BackgroundCircular RNAs (circRNAs) have recently been found to be expressed in human brain tissue, and many lines ofevidence indicate that circRNAs play regulatory roles in neurodevelopment. Proliferation and differentiation of neural stem cells (NSCs) are critical parts during development of central nervous system (CNS).To date, there have been no reports ofcircRNA expression profiles during the differentiation of mouse NSCs. We hypothesizethat circRNAs mayregulate gene expression in the proliferation anddiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…CircRNAs are generally expressed in vast majority of human tissues and are especially highly expressed in human brain [18,40]. Furthermore, the expression of circRNAs always has a tissue-or cellspecific manner, which makes them a suitable candidate for biomarker studies in human cancer [10,19,20,41].…”
Section: Properties Of Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are generally expressed in vast majority of human tissues and are especially highly expressed in human brain [18,40]. Furthermore, the expression of circRNAs always has a tissue-or cellspecific manner, which makes them a suitable candidate for biomarker studies in human cancer [10,19,20,41].…”
Section: Properties Of Circrnasmentioning
confidence: 99%
“…High-throughput technologies have enabled in-depth characterization of circRNAs for identification and potential functions [15][16][17], such as ribosomal RNA depleted RNA sequencing, long-read sequencing and more importantly, improved circRNA mining bioinformatics algorithms. CircRNAs have been demonstrated as an abundant and conserved class of RNAs, and are widely expressed in a complex tissue-, cell type-or stagespecific manner [10,[18][19][20][21][22]. Recent studies confirmed the significant biological functions of circRNAs, especially in human cancers [23,24].…”
Section: Introductionmentioning
confidence: 98%
“…Neural stem cells (NSCs) existing in the subventricle zone of the brain's germinal region and the subgranular zone of the hippocampus are capable of self-renewing, proliferating, migrating, and differentiating into various types of cells within the brain and spinal cord tissue [13,41]. NSC differentiation into neurons, astrocytes, and oligodendrocytes could replace necrotic cells resulting from injuries to promote the structural and functional repair of the brain and spinal cord [50]. However, this self-renewal is not adequate for the recovery of neurological function after brain injury [1,32,47].…”
Section: Introductionmentioning
confidence: 99%
“…The third paper by Yang et al [3] focused on systems biology of gene expression on a different type of transcripts, circular RNAs (circRNAs). There have been no reports of circRNAs expression profiles during the differentiation of mouse neural stem cells (NSCs) and the authors tried to find the possible regulatory roles of cir-cRNAs in the differentiation.…”
Section: The Science Program For the Icibm 2018 Systems Biology Trackmentioning
confidence: 99%